Bionutritional efficiency and carcass characteristics of confined steers receiving different nitrogen sources with whole or milled corn - Klein, John Lenon; Machado, Diego Soares; Porsch, Renata Volpatto; Brondani, Ivan Luiz; Alves Filho, Dari Celestino; Moura, Amanda Farias de; Cardoso, Gilmar dos Santos; Silva, Adrieli Linhat da; Domingues, Camille Carijo; Silva, Marcelo Ascoli da (Semina: Ciências Agrárias, 2018)
The objective of this study is to evaluate the bionutritional efficiency and carcass characteristics of confined steers receiving different nitrogen sources associated or not with corn grain processing in the diet. The study used a completely randomized design with a 3?? 2 factorial arrangement. Fifty-three Charolais and Nellore crossbred steers were used, with a mean age of 22 Â± 0.23 months and initial weight 250 Â± 15.80 kg. The animals were randomly divided into the following treatments: soybean meal + whole corn, soybean meal + milled corn, conventional urea + whole corn, conventional urea + milled corn, slow-release urea + whole corn, and slow-release urea + milled corn. A roughage: concentrate ratio of 50: 50 was used. The steers were confined until reaching a weight of 420 kg. The slaughtering occurred according to the schedule of the commercial slaughterhouse. Feed efficiency was lower in animals receiving slow-release urea than those fed true protein. The steers fed soybean meal presented a higher Kleiber ratio and higher nutritional index compared to those receiving conventional or slow-release urea. The provision of soybean meal promoted higher production of rib meat and meat with a higher L* compared to those receiving urea, and better carcass finish compared to those receiving slow-release urea. Diets with milled corn increased warm and cold carcass yields and decreased weight loss during carcass chilling. Total replacement of soybean meal with conventional or slow-release urea reduced the biological efficiency of steers. The supply of milled corn in the concentrated fraction increased carcass yield.